Modelo didáctico de indagación y actitud científica hacia el área de Ciencia, Tecnología y Ambiente, en estudiantes del Primer Grado de Secundaria de la I.E. Simón Bolívar - Otuzco - Moya Rodríguez, Hunter Humer (2018)
ABSTRACT The purpose of the present investigation was to determine the effect of the application of a model of inquiry in the development of the scientific attitude towards the Area of Science, Technology and Environment in students of the first grade of Secondary School "Simón Bolívar" of Otuzco - 2007, with an explanatory, quasi-experimental design. The population was 92 students of the first grade of secondary of the I.E. Simón Bolívar- Otuzco, divided into 4 sections: a, b, c and d. The sample consisted of 48 students of first grade of secondary, being the experimental group the classroom C, with 24 students and the control group the classroom B, with 24 students to whom it was applied; the independent variable Scientific Attitude Inquiry Model towards the CTA area (EACTA). The results obtained through the hypothesis test indicate that the test value "t" found for the four dimensions is located to the right of the critical value 2.07 at 95% of confidence level and 5% of significance. So it is concluded that the application of the didactic model of the investigation in the teaching of the natural sciences, significantly developed the scientific attitude towards the CTA area, in the students of the 1st grade of secondary of the Simón Bolívar-Otuzco school; with an experimental "t" of 7.065 and a p-value <0.05 (0.000 <0.05).